2000
DOI: 10.1046/j.1460-9568.2000.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and origin of the calretinin‐containing innervation of the nucleus accumbens of the rat

Abstract: The nucleus accumbens of the rat consists of several subregions that can be distinguished on the basis of histochemical markers. For example, the calcium-binding protein calbindin D28k is a useful marker of the core compartment of the nucleus accumbens. Calretinin, another calcium-binding protein, is found in a dense fibre plexus in the accumbal shell and septal pole regions. The source of the accumbal calretinin innervation is not known. We examined the distribution of calretinin in the nucleus accumbens and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 76 publications
(206 reference statements)
3
19
0
1
Order By: Relevance
“…CRexpressing neurons, however, remained unchecked for their electrophysiological properties. Using triple immunostaining in coronal slices from CB1-tdT mice (n = 3), we observed strong and extensive CR signals in neuronal processes in the NAc shell, with very few CR-positive somas, as reported previously (31). For NAc/striatal MSNs, COUP TF1-interacting protein 2 (Ctip2) has been identified as a reliable molecular marker (32).…”
Section: Resultssupporting
confidence: 84%
“…CRexpressing neurons, however, remained unchecked for their electrophysiological properties. Using triple immunostaining in coronal slices from CB1-tdT mice (n = 3), we observed strong and extensive CR signals in neuronal processes in the NAc shell, with very few CR-positive somas, as reported previously (31). For NAc/striatal MSNs, COUP TF1-interacting protein 2 (Ctip2) has been identified as a reliable molecular marker (32).…”
Section: Resultssupporting
confidence: 84%
“…The light parvalbuminlabeling in the ventral region compared to the dorsal region is reminiscent of the pattern in rat, in which relatively low densities of parvalbumin-ir fibers and neurons are seen in the medial shell region as compared to more dorsolateral areas, including the core and caudate (Zahm et al, 2003). The intense calretinin labeling in the ventral region relative to the dorsal region in pigeons may correspond to stronger calretinin-ir in the shell region than the core region in rats (Tan et al, 1999;Bubser et al, 2000) and primates (Brauer et al, 2000). In the case of calbindin, although the labeling patterns in the pigeon nucleus accumbens are similar to those found in other avian species (Roberts et al, 2002;Bálint and Csillag, 2007), they clearly differ from those found in the mammalian accumbens.…”
Section: Comparison With Mammals Core and Shell Divisionsmentioning
confidence: 70%
“…In the case of calbindin, although the labeling patterns in the pigeon nucleus accumbens are similar to those found in other avian species (Roberts et al, 2002;Bálint and Csillag, 2007), they clearly differ from those found in the mammalian accumbens. Unlike birds, the shell region in mammals has low calbindin-ir compared to the core region; this is true for both rats (Tan et al, 1999;Bubser et al, 2000) and primates (Brauer et al, 2000; but see Meredith et al, 1996 for marmosets). Therefore, if one only considered evidence based on calbindin-ir, the dorsal and ventral regions of the avian nucleus accumbens are not directly comparable to the core and shell of the mammalian accumbens.…”
Section: Comparison With Mammals Core and Shell Divisionsmentioning
confidence: 99%
“…For calretinin immunostaining a polyclonal goat IgG antibody (Millipore; catalog #AB1550; lot #0603024584; 1:1,000) raised against purified guinea pig calretinin was used. This antibody recognized a specific band of about 31 kDa in the extracts of mouse brain (data not shown; Bubser et al, 2000) and produces specific staining in the OB in the pattern reported elsewhere (Bagley et al, 2007;De Marchis et al, 2007;Whitman and Greer, 2007). For Pax6 immunostaining a polyclonal rabbit IgG antibody (Covance, Princeton, NJ; catalog #PRB-278P, lot #14942001; 1:3,000) raised against the peptide (QVPGSEPDMSQYWPRLQ) derived from the C-terminus of the mouse Pax6 protein was used.…”
Section: Immunohistochemistrymentioning
confidence: 92%